Video Image Enhancement of CCTV Footage Using a Combination of Contrast Limited Adaptive Histogram Equalization (CLAHE) and Filtering Methods - Fahri, Syahrul; Taufik, Insan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The quality of CCTV video footage often deteriorates due to poor lighting conditions, unfavorable environmental factors, and limited hardware specifications. These issues can result in the loss of critical visual details, such as faces or monitored objects. This study aims to enhance the visual quality of CCTV video by combining the Contrast Limited Adaptive Histogram Equalization (CLAHE) method with several filtering techniques, including median, mean, and Gaussian filters. The video format used in this research is .mp4, and the image enhancement process is implemented through a desktop application developed using Visual Studio Code. The results demonstrate that the combination of CLAHE and filtering techniques significantly improves contrast and reduces noise, making previously obscured details more visible. This approach enables the developed application to effectively enhance video surveillance footage captured under suboptimal lighting conditions